Testing on Energy Absorption of Banana Fiber Polyester Composite - Mohamed, N.H.N; Juneh, H.; Yusof, M. (Scientific.Net, 2011)
Natural fibers are now becoming a subject of interest to replace synthetic fiber as reinforcement materials where the development of natural fiber composites has been conducted in the last few decades. The objective of this research is to investigate the energy absorption capacity of banana fiber polyester composite and its specific energy absorption capacity as well. Banana fibers are extracted and cut into 10mm, 20mm and 30mm fiber length. Fabrication of rectangular bar as composite samples with different banana fiber length and fiber volume fraction (1%, 2%, and 3%) were conducted and the results are studied and analyzed. The information on energy absorption and specific energy absorption capacity are useful for applications such as automotive structures where the ability to absorb impact may save life. The increase of banana fiber content and length shows an increase of maximum load and energy absorption values for all specimens.